Reality and the Method of Explaining Human Action in the Framework of the Islamic Philosophy A Fundamental Theory in the Humanities - Seyed Saeed Zahed (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
This article reviews the Reality and the Method of Explaining Human Action in the Framework of the Islamic Philosophy: A Fundamental Theory in the Humanities book.‌ To reach the Islamic civilization, the necessity for producing Islamic social science and humanities became obvious after Islamic Revolution.‌ Accordingly, several approaches were developed by different experts.‌ One of them is to produce Islamic social science on the basis of Islamic Philosophy.‌ The reviewed book tries to develop Islamic Humanities philosophy according to Molla Sadra’s philosophy.‌ Unfortunately, the writer, assuming 'human action' as the subject of the social science and humanities, uses the Sadra’s philosophy to introduce a new Islamic social science and humanities philosophy.‌ There are four well-designed chapters in the book. Starting form philosophy of the philosophy of Islamic humanities, the writer analyzed 'human action fact' according to an assumed framework of Sadra’s philosophy. Fundamental philosophic assumptions are presented in the third and some methodological findings in the last chapter. However, the writings need to be reviewed according to Persian literature; some new understandings have been resulted.‌ The necessity of Islamic social science, the multiplicity of individual, society, social science and humanities, the importance of agency and structure according to Molla Sadra’s view, and gradual evolution of them are the findings of the book. Meanwhile, the book produces some valuable lights and shades on analyzing individual, society and social science using Molla Sadra’s philosophy.